A Converged Blockchain and Artificial Intelligence Approach for Strengthening Transparency and Trust in Digital Enterprises - Novianti, Leoni; Azizah, Nur; Mardiana, Mardiana; Perez, Carlos (ADI Journal on Recent Innovation (AJRI), 2026)
Digital business ecosystems increasingly rely on advanced technologies to ensure transparency, security, and trust in operational processes. However, traditional centralized systems still struggle with issues such as data manipulation, lack of traceability, and weak auditability, which affect stakeholder confidence and operational efficiency. This study investigates the integration of Blockchain and Artificial Intelligence (AI) as a combined framework to enhance transparency and trust in digital business operations across modern en- terprise environments. A mixed-method approach was employed, combining systematic literature analysis with a case-based evaluation involving three digital service companies implementing blockchain and AI models. Quantitative assessment was conducted using performance metrics such as transaction processing time, data integrity validation, and trust perception index, based on survey responses from 120 stakeholders, system log analysis across three digital service companies, and expert validation involving 15 industry specialists. Findings reveal that integrating blockchain with AI improves operational transparency by 42 percent, reduces data verification time by 35 percent, and increases stakeholder trust levels by 48 percent compared to conventional systems. The model demonstrates improved audit trails, decentralized decision-making, and enhanced anomaly detection accuracy in business data processes. The fusion of blockchain and AI offers a promising technological architecture capable of strengthening digital governance, increasing trust, and supporting secure business transformation. This research provides theoretical and practical implications for enterprises adopting emerging technologies toward sustainable and ethical digital operations, aligning strongly with digital transformation goals and SDG principles.